Styrene-free water-thinnable unsaturated polyester resins with hydrophilic sulfonate groups for coating applications. Part II. Syntheses carried out via copolymerization - Jankowski, P.; Rokicki, G. (Polimery, 2021)
The new UV-curable styrene-free water-thinnable polyester resins with hydrophilic sulfonate groups were obtained in copolymerization processes. Sodium salt of 3-hydroxy-1-propenesulfonic acid (1) (Scheme A, Fig.1) or sodium salt of 2,3-dihydroxypropanesulfonic acid (2) (Scheme B) and crosslinking monomer with allyl group as well as diols and acid anhydrides, commonly used in unsaturated polyester resins' preparation, were used in the syntheses. The processes were carried out at mild temperature (Table 1). Aqueous emulsions of the resins obtained were prepared and cured with UV radiation. Dependently on the sulfonate monomer used, its content in polyester and aqueous emulsion final composition the flexible coatings, showing hardness in the range 125-312 (by Persoz pendulum) and good adhesion to the glass or metal (Table 2), useful for applications as coatings for glass, wood or metal were obtained.